Twenty natural organic pigments for application in dye sensitized solar cells - Obregón, D. (2017)
In this work we present the results of a study of twenty natural pigments obtained from plants and insects from southern Ecuador. Many of them will be considered as a potential natural sensitizer for the construction of DSSCs. The results indicate that these pigments have a good performance in the absorbance and wavelength spectra. Were selected four best pigments for the construction of DSSCs, Rumex tolimensis Wedd, Raphanus sativus, Hibiscus sabdariffa, and Prunus serótina, however the conversion efficiency is lower than 1%.